Status Hukum Pengungsi di Indonesia: Antara Pihak Non-Negara dan Prinsip Non-Refoulement - Beni Prawira Candra Jaya; Zainal abdul aziz hadju; Vincent Godana Yatani; Ninin Ernawati (Unram Law Review, 2025)
Indonesia, a key player in global migration flows, has not ratified the 1951 Refugee Convention or the 1967 Protocol, creating uncertainty regarding the legal status and protection of refugees. This article examines how Indonesia, as a non-signatory, upholds the principle of non-refoulement, a core element of customary international law. Using a normative legal approach, including doctrinal analysis and policy evaluation, the study explores Indonesia’s national regulations, particularly Presidential Regulation No. 125 of 2016 on refugee handling, and its cooperation with UNHCR in Refugee Status Determination. Findings indicate that while Indonesia is not legally bound by the Refugee Convention, it adheres to fundamental humanitarian principles, including the prohibition of forced return. However, the lack of a national asylum system limits refugees’ access to legal protection, basic rights, and long-term security. This article highlights the importance of strengthening Indonesia’s domestic legal framework to ensure alignment with international protection standards, offering a contribution to the literature by emphasizing the necessity of a robust asylum system in a non-signatory state.